STRATEGI SEKTOR PERTANIAN DALAM MENGHADAPI INFLASI TANAMAN PANGAN DI KABUPATEN LAMPUNG TENGAH - Yuliana Saleh; Wan Abbas Zakaria; Eka Kasymir (Indonesian Journal of Socio Economics, 2019)
This study aims to determine the factors that influence the inflation rate and find out the strategy of the agricultural sector to deal with inflation of food crops in Central Lampung Regency. Data on superior crops of food crops refers to the Decree of the Minister of Agriculture of the Republic of Indonesia number 830/Kpts/Rc.040/12/2016, namely cassava, corn, soybeans, and rice. This study was analyzed using the Consumer Price Index (CPI) and Inflation Rate. The form of the agricultural sector strategy in order to deal with inflation of food crops is created from the results of the FGD.  Factors that influence the inflation rate in terms of production (supply) in Central Lampung Regency are high production costs, increases in prices of agricultural production facilities, rising labor costs, high distribution costs of agricultural products, inadequate infrastructure, weather and pest attacks plant diseases, and slow innovation in agriculture. The strategy of the agricultural sector in Central Lampung Regency is through intensification, extensification and rehabilitation programs that focus on agricultural innovation activities including: using superior varieties adapted to regional conditions, using irrigation systems (SRI), developing supply chain management systems, institutional engineering innovations and partnership, setting reference prices for superior agricultural commodities, using special planting machines for grains, processing cow manure into organic fertilizers, special efforts to increase production and increase in rice, corn, soybean, cassava, new paddy field printing programs, and optimal use of fertilizers.  Keywords: inflation, agricultural sector, strategy